Antianginal effectiveness and tolerability of ivabradine in patients with stable angina: CONTROL-2 Study results - Yu. A. Karpov; M. G. Glezer; Yu. A. Vasyuk; R. T. Saygitov; E. L. Shkolnik (Кардиоваскулярная терапия и профилактика)
Aim. To compare the effectiveness of the combination therapy with ivabradine and β-adrenoblockers (β-AB) and the dose-titration β-AB therapy. Material and methods. This multi-centre, open, controlled study included 1104 patients with functional Class (FC) II-III stable angina (SA), sinus rhythm, and heart rate (HR) ≥60 bpm, who received regular β-AB therapy in submaximal doses. The participants were divided into the standard therapy group (β-AB therapy with the dose titration to the maximal tolerated dose; 228 patients (20,7%)) and the ivabradine therapy group (876 patients (79,3%))Results. Both groups were comparable by main demographical and clinical characteristics. Adding ivabradine to the β-AB therapy resulted in a more pronounced HR reduction at Week 16, compared to the standard therapy group (61±6 vs. 63±8 bpm; p=0,001). By the end of the study, the percentage of the patients with FC I SA was significantly higher in the ivabradine group than in the standard therapy group (37,1% vs. 28%; p=0,017). The average number of angina attacks between Weeks 8 and 16 was significantly lower in the ivabradine group than in the standard therapy group – 4 (2;10) vs. 6 (2;15), respectively (p=0,015). In the standard therapy group, the incidence of adverse events, such as dyspnoea, hypotension, and fatigue, was significantly higher than in the ivabradine group – 18,4% vs. 9,4%, respectively (p<0,001). Conclusion. In SA patients, the combination therapy with β-AB and ivabradine demonstrated good tolerability, safety, and high antianginal effectiveness, which resulted in a more pronounced clinical improvement, compared to the dose-titration β-AB therapy.